Jenkins continuous integration cookbook : over 90 recipes to produce great results from Jenkins using pro-level practices, techniques, and solutions /: over 90 recipes to produce great results from Jenkins using pro-level practices, techniques, and solutions. (2015) - Berg, Alan Mark
No abstract available